1991
DOI: 10.1073/pnas.88.24.11564
|View full text |Cite
|
Sign up to set email alerts
|

Receptor class desensitization of leukocyte chemoattractant receptors.

Abstract: To better define their regulation,.tide and CSa chemoatacnt receptor cDNAs were t t expressed with high efficiency (...35-54%) in human kidney cefls. As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 53 publications
7
74
0
Order By: Relevance
“…Following lysis and extraction for 10 min while rotating at 4°C, samples were centrifuged at 15,000 ϫ g for 15 min at 4°C to remove insoluble debris. The supernatant was added to 10 mg of protein A-Sepharose that had been precoated with 15 l of a rabbit antiserum directed against the C-terminal 12 amino acids of the FPR. The use of this antibody for immunoprecipitating the photoaffinity-labeled FPR has been previously described (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following lysis and extraction for 10 min while rotating at 4°C, samples were centrifuged at 15,000 ϫ g for 15 min at 4°C to remove insoluble debris. The supernatant was added to 10 mg of protein A-Sepharose that had been precoated with 15 l of a rabbit antiserum directed against the C-terminal 12 amino acids of the FPR. The use of this antibody for immunoprecipitating the photoaffinity-labeled FPR has been previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the homologous desensitization of chemoattractant receptors, where a ligand desensitizes only its own receptor, heterologous desensitization, where an activated receptor desensitizes one or more other inactive receptors, has also been demonstrated to occur between chemoattractant receptors (14,15). This latter form of desensitization is at least in part mediated by second messenger-activated kinases, such as protein kinase C (11).…”
mentioning
confidence: 99%
“…The mutated DNA fragments obtained were digested with BssHII and ApaI and cloned into the expression vector pRK5 (24) containing the ␣ 1B AR cDNA. Recombinant clones were isolated and sequenced by cycle sequencing using Exo Ϫ Pfu polymerase (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…nomenon termed class desensitization (38,39). Recently, it was shown that PLC␤3 was phosphorylated both by PKC and PKA mediated pathways (25) and PLC␤2 was phosphorylated by PKA (24).…”
Section: Fig 4 Desensitization Of Cxcr4mentioning
confidence: 99%